Evaluation of Alveolar Bone Density at Furcation Sites Using Computer Tomography in Patients with Horizontal Bone Loss - Dumitrescu, Alexandrina L.; Zetu, L.; Teslaru, S.; Haba, D. (The Journal of Dentists, 2014)
Objectives: The aim of the current study was to evaluate quantitatively bone density in the maxillary and mandibular interradicular sites and to establish his determinants as assessed on computer tomography images. Methods: Sections of 0.5 mm thickness horizontal CT sections were selected to measure bone density of the interradicular and interdentally septum in CTs from 29 individuals (17 females, mean age 40.44 years). Results: There were statistically significant differences of mean value and of bone density at specific bone depth levels in the furcation area according to age, gender, tooth type and between the maxilla and mandible (P < 0.05). The multiple linear regression analyses showed, for both mean furcation alveolar bone density value as well as particular values at different bone level as dependent variable, a strong association with gender, distance from the furcation roof to the alveolar bone septum, presence of restorative treatment of caries, presence of endodontic treatment and mean alveolar bone density of the mesial and distal alveolar septum (P < 0.0001). Conclusions: Using the CT in periodontology has demonstrated to be a valid support to diagnose the changes in the alveolar bone, to monitor the treatment results with a higher precision and to point out possible error sources.